THE IMPACT OF ARTIFICIAL INTELLIGENCE IN SUPPORTING RISK MANAGEMENT AND PERFORMANCE EVALUATION - Ali Mirzah Abd- Alhamza Al-Issawi (Scholar Express Journals, 2024)
The rapid development of technology has led to a greater reliance on Artificial Intelligence (AI) programs across various industries. As a result, this research aims to investigate the role of AI in supporting risk management within institutions and its impact on performance evaluation. The study utilized a descriptive analytical approach and designed a 38-item questionnaire with three main sections: AI and management, risks, and performance evaluation. The findings highlighted the significant role of AI in supporting both risk management and performance evaluation. The study emphasizes the importance of leveraging AI applications for decision-making processes and performance evaluation, as well as staying updated on technological advancements in the field.
Keywords: Artificial Intelligence; Risk Management; Performance Evaluation